A Correlation-Regression Statistics: Predicting Uniaxial Compressive Strength from Point Load Index for Hydrothermal Clay Materials - Muhammad Alfiza Farhan; Akbar Aprian (Jurnal Teknologi Pertambangan, 2026)
This study addressed the difficulty of determining uniaxial compressive strength in hydrothermally altered breccia, where preparing intact core samples was not feasible. A field-based approach using point load index measurements was adopted to provide an alternative means of estimating rock strength. Twenty-one representative breccia samples from Pit C were tested through standardized point load procedures and laboratory uniaxial compression tests. Linear regression analysis was performed to examine the relationship between the two strength parameters. The results showed a strong and statistically significant linear trend, indicating that point load index values could reliably predict uniaxial compressive strength for the altered breccia. The analysis further demonstrated that most strength variability was explained by the regression model. These findings supported the use of point load testing as an efficient and practical method for strength estimation in geological conditions where conventional testing was limited.